EVALUATING THE EFFECTIVENESS OF PHYSICAL AND ONLINE AWARENESS CAMPAIGNS IN ENHANCING UNDERSTANDING OF SPEECH AND LANGUAGE DELAYS AMONG UNIVERSITY STUDENTS - Usman Jaffer; Desmond Wong Kim Fei; Farah Hani Faizul; Rabiatul Adawiyah Rahmat; Nurul Nabilah Mohd Fuad; Nurul Puteri Hidayah Mohd Azemi; Ulya Mufidah Amir Hamzah; Che Mohd Nasril Che Mohd Nassir; Mohamed Ayaaz Ahmed; Rahmah Ahmad H. Osman (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
This study assesses the effectiveness of physical and online awareness campaigns in increasing understanding of speech and language delays within the International Islamic University Malaysia (IIUM) community. Utilizing a quasi-experimental design, 35 IIUM students participated in an intervention comprising social media engagement and an exhibition-like physical campaign. Pre-test and post-test surveys measured the level of understanding, revealing a significant increase in comprehension (pre-test M=20.3, post-test M=32.0, t(34)=8.74, p<.001). Thematic analysis of participant feedback identified key themes including learning outcomes, quality of information, misconception reduction, presentation quality, and overall positive experience. Findings align with existing literature, demonstrating that well-designed awareness campaigns effectively enhance knowledge and reduce stigma associated with speech and language delays. However, limitations such as a small sample size and lack of validated measurement tools suggest the need for further research. This study underscores the importance of multifaceted awareness strategies in promoting early diagnosis and intervention, ultimately contributing to improved developmental outcomes for affected children.